2023
DOI: 10.1002/anie.202306824
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli‐Responsive PROTACs for Controlled Protein Degradation

Abstract: Proteolysis Targeting Chimeras (PROTACs) represent a promising therapeutic modality to address undruggable and resistant issues in drug discovery. However, potential on‐target toxicity remains clinically challenging. We developed a generalized caging strategy to synthesize a series of stimuli‐responsive PROTACs (sr‐PROTACs) with diverse molecular blocks bearing robust and cleavable linkers, presenting “turn on” features in manipulating protein degradation. By leveraging pathological cues, such as elevated ROS,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 53 publications
(95 reference statements)
0
8
0
Order By: Relevance
“…Based on the various membrane receptors on the cell surface in the targeted tissue, folate-caged, 18,19 aptamer-conjugated, 20,21 and antibody-conjugated 22,23 PROTACs have been widely developed to facilitate PROTAC drug delivery by receptor-mediated endocytosis. To enable discrete control over PROTACs’ function, some labile protecting groups (such as photo-activated 24–26 and hypoxia-activated 27 ) have been installed on the POI ligands 24,27 or E3 ligase ligands 25,26,28 to form stimuli-responsive caged PROTACs. For example, after light exposure with a specific wavelength, the optical activation of small molecule-induced protein degradation was observed in terms of photo-caged PROTACs.…”
Section: Building-block Design and Smart Protac Prodrug Nanoparticlesmentioning
confidence: 99%
“…Based on the various membrane receptors on the cell surface in the targeted tissue, folate-caged, 18,19 aptamer-conjugated, 20,21 and antibody-conjugated 22,23 PROTACs have been widely developed to facilitate PROTAC drug delivery by receptor-mediated endocytosis. To enable discrete control over PROTACs’ function, some labile protecting groups (such as photo-activated 24–26 and hypoxia-activated 27 ) have been installed on the POI ligands 24,27 or E3 ligase ligands 25,26,28 to form stimuli-responsive caged PROTACs. For example, after light exposure with a specific wavelength, the optical activation of small molecule-induced protein degradation was observed in terms of photo-caged PROTACs.…”
Section: Building-block Design and Smart Protac Prodrug Nanoparticlesmentioning
confidence: 99%
“…have made significant advancements in the field of controllable targeted drug design by developing a novel radiation-responsive PROTAC prodrug NGP-25 (Fig. 10 C) for traceless release [ 77 ]. This innovative approach utilizes carbamate-bearing cages that exhibit excellent chemical and proteolytic stabilities, ensuring the stability of NGP-25 in blood.…”
Section: Small-molecule Protac Prodrugsmentioning
confidence: 99%
“…D Chemical structures of the enzyme-responsive PROTAC (adapted from [ 82 ]). E Chemical structures of the enzyme-responsive PROTAC (adapted from [ 77 ]) …”
Section: Small-molecule Protac Prodrugsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate if the liposomal PROTAC prodrug could deplete STAT3 in HCC-derived CSCs, we incubated hepa1-6-derived CSCs with inS3, inS3 + VL, and inS3-TEG-VL and found that only inS3-TEG-VL treatment induced obvious reduction in the STAT3 levels, suggesting that inS3-TEG-VL was responsible for degrading CSC-intrinsic STAT3 rather than those separated components (Figure L). WB analysis also revealed a positive correlation between STAT3 deletion efficacy and the inS3-TEG-VL dose, which could be explained by the catalyst-like protein-degrading properties according to previous reports , (Figure J,K). The PROTAC-dependent STAT3 deletion was highly efficient, as a low inS3-TEG-VL dose of 3.2 μM almost abolished STAT3 in hepa1-6-derived CSCs, which was selected as the standard condition for subsequent in vitro and in vivo analyses.…”
mentioning
confidence: 99%